Periodic normal forms for bifurcations of limit cycles in DDEs - Lentjes, Bram; Spek, Len; Bosschaert, Maikel M.; Kuznetsov, Yuri A. (Academic Press Inc., 2025)
A recent work [1] by the authors on the existence of a periodic smooth finite-dimensional center manifold near a nonhyperbolic cycle in delay differential equations motivates the derivation of normal forms. In this paper, we prove the existence of a special coordinate system on the center manifold that allows us to describe the local dynamics on the center manifold near the cycle in terms of periodic normal forms. To construct the linear part of this coordinate system, we prove the existence of time periodic smooth Jordan chains for the original and adjoint system. Moreover, we establish duality and spectral relations between both systems by using tools from the theory of delay and Volterra integral equations, dual perturbation theory, duality theory, and evolution semigroups.
Keywords: Center manifold; Delay differential equations; Jordan chains; Nonhyperbolic cycles; Normal forms; Sun-star calculus; Taverne; Analysis; Applied Mathematics